PENCEGAHAN AGRESIVITAS SISWA SMPS KRISTEN BNKP TELUKDALAM MELALUI LAYANAN INFORMASI BERBANTUAN MEDIA AUDIOVISUAL - Sesilianus Fau (Institut Pendidikan Tapanuli Selatan, 2022)
This research was based on the aggressive assorted behaviours of the students, and the lack of the teacher role of guidance and counseling in giving information services using audiovisual media to the students of SMPS Kristen BNKP Telukdalam. The objectives of this research were 1) to describe the level of students’ aggression before using the audiovisual media in giving the information services; 2) to describe the level of students’ aggression after using the audiovisual media; and 3) to test the effectiveness of the audiovisual media in giving the information services to avoid the aggression of the students. This study was a quantitative research which was designed by using Pre-Experimental design that is the one group pretest-posttest design. The population of this research was the eighth grade students of SMPS Kristen BNKP Telukdalam. The purposive sampling technique was used to have the sample of this study that is 27 students as the result of documentation analysis (students’ case book) and the result of interview. The result of this research showed that 1) the aggression of the students before they were given information services using audiovisual media was in medium level with average score is 95,6 or 63,8 %; 2) the aggression of the students after they were given information services using audiovisual media was in low level with average score 68,3 or 45,5%; 3) the result of the analysis showed that T-test (378) ≥ T-table (107) and Z-test (4,542) ≥ α (0,05). It can be concluded that Ho is refused and Ha is accepted. In other words, information services using audiovisual media have positive effect to avoid the aggression of students of SMPS Kristen BNKP Telukdalam.